2012
DOI: 10.1111/bjd.12005
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral distribution of nonmelanoma skin cancer between older Hispanic/Latino and non-Hispanic/non-Latino individuals

Abstract: NMSC appears to be more common on the left side of older non-Hispanic/non-Latino individuals, while it is more common on the right side of older Hispanic/Latino individuals. This is likely to be secondary to an environmental factor, such as ultraviolet radiation. NMSC is significantly more common in males relative to females, which may be attributed to differences in gender roles or referral practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The pattern has been demonstrated in two studies of NMSC and one of melanoma. Two are US based, the first involving a cohort from Latino/Hispanic descent presenting with NMSC [ 27 ]. The second showed an increased prevalence of right-sided melanoma in women presenting on specific anatomical sites, namely, MIS of the ear/trunk and invasive melanoma of the eyelid [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern has been demonstrated in two studies of NMSC and one of melanoma. Two are US based, the first involving a cohort from Latino/Hispanic descent presenting with NMSC [ 27 ]. The second showed an increased prevalence of right-sided melanoma in women presenting on specific anatomical sites, namely, MIS of the ear/trunk and invasive melanoma of the eyelid [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For melanoma, it is higher among whites (2.9% in men, 1.9% in women) than in Hispanics (0.52% in men, 0.51% in women) [1, 4]. A study conducted in Miami showed that, among 3000 cases of nonmelanoma skin cancer reviewed, 60.1% were diagnosed in whites and 38.4% were diagnosed in Hispanics [5]. Findings using the Southeastern Arizona Skin Cancer Registry showed that the rates for nonmelanoma skin cancer in whites were approximately 11 times greater than rates for Latinos [6].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Previous perception has remained that skin cancer risk in Hispanics and Asians is lower than that in whites. 2,4 Hispanics may have more protection from the sun because of darker skin type and increased melanosome activity, 7,8 whereas Asians may be culturally, historically, and cosmetically inclined to keep away from the sun to maintain a lighter complexion. 9,10 However, despite historically lower rates of skin cancer, in recent years, skin cancer incidence in these groups has reportedly been increasing.…”
mentioning
confidence: 99%